Digital Wellness Framework for Online Learning - Palalas, Agnieszka; Doran, Mae (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
The ever-changing digital context, digital habits and pressures, demands and practices, often contribute to online learners experiencing burnout, stress, fatigue, sleep deprivation, cognitive overwhelm, and work-life imbalance, just to mention a few issues identified in literature. With the rise of online learning offerings, an increasing number of educators across diverse contexts and disciplines are faced with questions pertaining to the optimal experience and design for online learning. Current research has highlighted both positive and negative impacts of teaching and learning in the digital space. This online learning design debate has identified a need for practices that contribute to the holistic wellbeing of learners rather than merely cognitive outcomes. There is a need for an evidence-based pedagogical framework centred on wellbeing that enables the creation of learning “by design”. This research, applying secondary data analysis and a mindfulness-informed lens, results in such a framework, i.e., the DW-FOLD: Digital Wellness Framework for Online Learning – to guide intentional use of technology and online learning pedagogical principles that ensure active and meaningful learning while using technology for the good of all learners.